TMS-EEG Biomarkers of Amnestic Mild Cognitive Impairment Due to Alzheimer’s Disease: A Proof-of-Concept Six Years Prospective Study - Ferreri, Florinda; Guerra, Andrea; Vollero, Luca; Ponzo, David; Määtta, Sara; Könönen, Mervi; Vecchio, Fabrizio; Pasqualetti, Patrizio; Miraglia, Francesca; Simonelli, Ilaria; Corbetta, Maurizio; Rossini, Paolo Maria (Frontiers in Aging Neuroscience, 2021)
Background: an Eearly and affordablye identification of subjects with amnesic mild cognitive impairment (aMCI) who will convert to Alzheimer’s disease (AD) is a major scientific challenge. Objective: tTo investigate neurophysiological hallmarks of sensorimotor cortex function in aMCI, under the hypothesis that some may represent plastic rearrangements induced by neurodegeneration, hence, predictors of future conversion to AD. We sought to determine (1) whether the sensorimotor network shows peculiar alterations in aMCI patients, and (2) if sensorimotor network alterations predict long-term disease progression at the individual level. Methods: Wwe studied several transcranial magnetic stimulation (TMS)-EEG correlates parameters of the sensorimotor cortex in a group of aMCI and followed the patients for 6 six years. We then identified aMCI who clinically converted to AD (pAD-MCI) and those who remained cognitively stable (npAD-MCI). Results: Motor cortex excitability was reduced in aMCI subjects compared to Controls. Moreover, we found a sensorimotor-specific disruption of local EEG synchronization, specifically in beta and gamma bands, which discriminate pAD-MCI from npAD-MCI. Finally sDA, a parameter related to the waveform shape of scalp signals and reflecting time-specific alterations in TMS-induced activity, predicted the conversion from aMCI to AD with high accuracy. Discussion: sSpecific cortical changes reflecting deficits of synchronization within the cortico-basal ganglia-thalamic-cortical loop in aMCI may reflect pathological processes underlying AD. These changes could be tested in larger cohorts as possible neurophysiological biomarkers of AD. Keywords: Mild Cognitive Impairment; Alzheimer’s disease; EEG; Navigated Transcranial Magnetic Stimulation; Biomarkers; nTMS-EEG.